Tick-Borne Rickettsioses in the Iberian Peninsula - Moerbeck, Leonardo (2022)
Tick-borne rickettsioses (TBR) are caused by obligate, intracellular bacteria of the spotted-fever group (SFG) of the genus Rickettsia (Order Rickettsiales), transmitted by hard ticks. TBR are one of the oldest known vector-borne zoonoses and pose a threat to both human and animal health, as over the years, new SFG Rickettsia spp. have been reported worldwide with the potential to be human pathogens. In Portugal and Spain, the countries that constitute the Iberian Peninsula, reported TB rickettsiae causing human disease include Rickettsia conorii conorii, Rickettsia conorii israelensis, Rickettsia slovaca, Rickettsia raoultii, Candidatus Rickettsia rioja, Rickettsia sibirica mongolitimonae, and Rickettsia monacensis. An allochthonous case of TBR caused by Rickettsia massiliae, described in Spain, points to the need to monitor disease epidemiology, to predict risks of exposure and spread of disease, and taking into account globalization and climate changes. This review aims to provide up-to-date information on the status of TBR in the Iberian Peninsula, as well as to show the importance of a national and international collaborative epidemiology surveillance network, towards monitoring Rickettsia spp. circulation in both Portugal and Spain.